Living diversity - shaping society. The opportunities and challenges posed by cultural difference in Germany. - (:unkn) unknown (My University, 2018)
Religious, cultural and linguistic diversity has always been a reality in Germany. Yet determining what constitutes success in terms of dealing with diversity on a day-to-day basis is a matter often subject to debate. Demonstrating respect for each other while living together in diversity must be cultivated but also involve the active participation of everyone affected. We experience diversity every day in our communities: in our neighborhoods, schools, at work and in our free time. The publication accompanying the Reinhard Mohn Prize 2018 offers insight into how Germany can effectively target living well together in a multicultural society marked by social inclusion and respect for diversity. It analyzes current approaches in Germany, examines good practices found in other countries and recommends actions that can be taken to cultivate a positive experience with diversity. Contributions by distinguished authors such as Armin Nassehi, Doug Saunders and Bart Somers explore the issue from various viewpoints.
Keywords: Gesellschaftsordnung; Einwanderung; Bevölkerungsentwicklung; Urbanität; Migration; Zusammenleben; Inklusion; Religionsgemeinschaft; Populismus; Internationaler Vergleich; Kulturelle Vielfalt; Diversity Management; Multikulturalismus; Leitkultur